Las técnicas grafo plásticas en el desarrollo de la motricidad fina bajo el eje transversal de la interculturalidad en la educación inicial 1, del C.I. Municipal San Alfonso de Riobamba, periodo 2022 – 2023 - Salazar García, Andrea Paola (2023)
ABSTRACT: The objective of this research was to determine the incidence of plastic graph techniques in the development of fine motor skills under the transversal axis of interculturality in Initial Education 1 of the C.I. Municipal San Alfonso de Riobamba, Ecuador, period 2022 - 2023. The investigation was based on references where information collected from reliable bibliographic documents and direct observation at the scene of the events are taken into account, for which it was developed within a quantitative approach, with a descriptive, field, cross-sectional and correlational design with the applied research method. As a technique for collecting information, observation and the survey were used, which allowed the variables investigated to be related. As an instrument, an observation sheet and a questionnaire were designed respectively. The observation sheet was applied based on the objectives applied in the classroom and the interview was implemented with the teachers. Taking into account that we worked with a sample of 25 children and 7 teachers. According to the results, it was determined that the children of Initial Education 1 have not yet been able to develop fine motor skills and the teachers evidenced the importance of being trained and receiving training and updating in the use of resources, materials and adequate techniques to achieve this. purpose in the classroom at this educational level. As a result, it can be pointed out that there are problems in the correct development of fine motor skills through appropriate plastic graph techniques. In view of which, it was concluded that it was necessary to design a proposal as a solution to the problem detected in relation to the lack of training for teachers and the lack of resources, materials and activities that facilitate the application of plastic graph techniques in the development of fine motor skills, helping children achieve a full and comprehensive education through a quality educational process. Key words: Techniques, plastic graph, fine motor skills, interculturality.